The Effect of Capital Structure and Dividend Policy on Firm Value: Financial Performance as a Mediator in Indonesian Food and Beverage Companies - Nadia Zahrani; R. Ramlawati; J. Jayadi (Golden Ratio of Data in Summary, 2026)
This study analyzes the effect of capital structure and dividend policy on firm value with financial performance as a mediating variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The objective of this research is to examine both the direct and indirect effects among the variables. This study employs a quantitative research approach using secondary data obtained from 16 companies selected through purposive sampling. Data analysis was conducted using SmartPLS 4. The results indicate that capital structure does not have a direct effect on firm value but has a positive effect on financial performance. Dividend policy has a negative effect on firm value but does not affect financial performance. Financial performance has a positive and highly significant effect on firm value. Furthermore, financial performance fully mediates the relationship between capital structure and firm value but does not mediate the relationship between dividend policy and firm value. In conclusion, profitability plays a crucial role in enhancing firm value.